Geopolitics and Business - Nestorović, Čedomir. author. (orcid)0000-0001-7160-1776 Link aut Link
XI, 317 p.
Keywords: This book sheds light on the intricate relationship between geopolitics and business and the essential interdependence between corporations and geopolitics. Despite apparent animosity, practical solutions and theories proposed by geopolitics find resonance within the business world, and vice versa. Concepts like critical theory, disruption, hegemony, strategic rivalry, and cost-effectiveness hold common ground in both realms, even though they have historically been disregarded. Geopolitical authors have often overlooked the vital role played by businesses in shaping global affairs, while businesses themselves view geopolitics as a risk to be managed. These contrasting viewpoints have given rise to misunderstandings and misconceptions between the two spheres. The author sets out to bridge the gap between geopolitics and business, exploring how corporations perceive space, state, and power, while also analyzing the influence of classical, critical, and feminist geopolitics on business strategies. This comprehensive analysis reveals that businesses are not mere non-state agents among many, but indeed, the principal non-state agents in geopolitics. The book is an essential read for scholars, researchers, and professionals seeking a deeper understanding of the dynamic interplay between these critical forces.